Convergent allostery in ribonucleotide reductase - William C. Thomas (Nature Portfolio, 2019)
Ribonucleotide reductase (RNR) catalyzes the conversion of ribonucleotides to deoxyribonucleotides, which is an essential step in DNA synthesis. Here the authors use small-angle X-ray scattering, X-ray crystallography, and cryo-electron microscopy to capture active and inactive forms of the Bacillus subtilis RNR and provide mechanistic insights into a convergent form of allosteric regulation.